Effect of coupling in steel/aluminium laminate subjected to tensile load and bending load - Pak, Jun Wei (Nanyang Technological University, 2022)
This project involves the study of coupling effects in steel/aluminium metal laminate composite when subjected to either tensile or bending loads. The finite element analysis software, ANSYS Workbench, was used for simulation and analysis of the structural response of the composite model. The finite element model used in this study was referenced from existing published research about coupling effects in composites and takes the form of a cantilevered laminate plate with the dimension: 500mm x 200mm 2.72mm, length, width, and thickness respectively. 3 cases were simulated and analyzed to determine how different parameters affect coupling responses in laminated structures. Case 1 made a comparison between the composite and the individual constituent metals which showed that the metal composite is a good choice for aerospace materials. In cases 2 and 3, the number of plies in the composite was varied from 2 to 8 layers to determine the structural response when the composite was subjected to a tensile or bending load. It was found that for both types of load, by increasing the number of plies, the structural stiffness of the laminate increases.